Anxiety, Self-Efficacy, And Self-Regulation in High School Students: The Mediating Role of Attentional Control - YÜKSEL, MÜGE (My University, 2024)
Reducing anxiety, developing self-efficacy and self-regulation skills, and increasing attentional control are among the goals of psychological counseling sessions. This study intends to determine whether or not high school students’ attentional control over their anxieties is affected by self-efficacy and self-regulation, as attentional control is not seen to have been studied correlationally with other variables in Turkey. 170 girl, 155 boys, total 325 students in Istanbul participated in the research. Data has been collected using the General Self-Efficacy Scale, the Perceived Self-Regulation Scale, the State-Trait Anxiety Inventory, and the Attentional Control Scale. Data were collected in classrooms. Correlation and path-analysis techniques have been used in analyzing the data. According to the findings, self-efficacy is a positive and significant predictor of self-regulation and attentional control and a negative predictor of anxiety in model for the high school students. Attentional control also negatively predicts anxiety. Additionally, attentional control has a partial mediating role between self-efficacy and anxiety.
Keywords: Anxiety; Attentional Control; Adolescents; Self-Efficacy; Self-Regulation